Stress Testing, Disclosure and Risk-Taking of Banks in Ghana - Kuranchie-Pong, L. (University of Ghana, 2013)
The occurrence of the global financial crisis has caused stress testing to receive much attention by regulators, bank management, rating agents and many others in the banking industry. Many investors lost confidence in the banking system after the occurrence of the global financial crises. The central banks have been employing stress testing to restore the confidence in the banking system in their countries. Stress testing is now a popular risk management tool. It is in this light that this study investigates the effect of stress testing, and disclosure on risk-taking of banks in Ghana for the period 2007-2011. The study made use of a panel regression model and relate risk-taking to disclosure, controlling for bank size, profitability, liquidity and treasury bill rate. Disclosure scores from a disclosure index are used to proxy for disclosure, likewise Z-score to proxy for total risk. Each control variable was dropped at a time to serve as a robust test of the regression result. The study also obtained primary data on stress testing to investigate stress test results influence on subsequent risk-taking behaviour of banks. Contrary to expectation, the regression results indicate that greater disclosure is associated with more risk-taking whiles lesser disclosure is associated with reduced risk-taking. Also, it was found that bank size is not important in influencing risk-taking behaviour of banks in Ghana. Besides, the researcher introduced treasury bill rate as a control variable for the first time and the results are economically meaningful and as well as statistically significant in influencing risk-taking of banks in Ghana. Again, the results reveal that greater percentage of the sample banks do not receive stress test results from the central bank (Bank of Ghana) hence relies mainly on their internal stress test results to influence their risk management policies. Also, not all the banks conduct internal stress test exercise. Stress testing is therefore a new phenomenon in banking industry of Ghana. Due to the occurrence of recent financial crises, stress testing, disclosures of information by banks to stakeholders have become very important. However, this is an area not researched in the Ghanaian context and a contribution to literature in this area and for policy makers is laudable. This study therefore, will broaden the approach and the design that can be used to research into the topic. Also, it will serve as a reference for future researchers to contribute to this area.
Thesis (MPHIL)-University of Ghana, 2013